Behavior of Hospital Health Workers and the Use of Personal Protective Equipment to Prevent Nosocomial Infections - Muhamma Ikbal Arif; Haderiah Haderiah; Sulasmi Sulasmi; La Taha; Ain Khaer (Health Notions, 2022)
One of the unexpected occurrences of activities in the hospital is nosocomial infection. Therefore, it takes attention from all hospital health workers regarding the behavior of the use of qualified Personal Protective Equipment (PPE) to protect themselves from the infection. The purpose of the study was to find out the relationship between the behavior of hospital health workers and the use of PPE to prevent nosocomial infections in Thalia Irham Hospital Kab. Gowa. This research was an analytic observational study with a cross sectional research design. A sample of 70 hospital health workers was determined based on the Lemesow formula, where sampling was carried out using a simple random sampling method. Data analysis was processed by Chi-square statistical test. The results of the analysis of the three variables studied had a significant relationship between knowledge (p-value = 0.000), attitude (p-value = 0.033), action (p-value = 0.027) and the use of PPE in preventing nosocomial infections. As conclusion, there is a relationship between the behavior of hospital health workers and the use of PPE in preventing nosocomial infections. Keywords: behavior; hospital health workers; nosocomial infection; personal protective equipment